Research progress of cerebral blood flow measured by arterial spin labeling in Alzheimer's disease - SUN Meng⁃fan; JIANG Ji⁃wei; WANG Yan⁃li; ZHANG Yuan; XU Jun (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Cerebral blood flow (CBF) changes are closely related to Alzheimer's disease (AD). Arterial spin labeling (ASL) uses water proton in blood as an endogenous contrast agent to obtain CBF, which has attracted must attention in AD studies due to its advantages of non⁃invasiveness and safety. However, there is still a lack of uniformity in the implementation of ASL in clinical settings, and limited by sample size and different population cohorts, research results may be different or lack of universality, which lead to the fact that this technology has not yet been widely applied in AD. This article reviews the new research progress on the correlation between CBF measured by ASL and AD disease process, pathologic biomarkers, vascular pathological burden, apolipoprotein E ε4 (ApoEε4) gene, and cognitive impairment development, in order to provide guidance for the clinical application of ASL in AD.